ALAT PENDETEKSI GAS AMONIAK PADA KAMAR MANDI BERBASIS ARDUINO (Studi Kasus di Hotel Wisma Menoreh Sampangan Semarang) - Achmad Abdul Charis (STEKOM PRESS, 2018)
This research generally aims to design a system that can overcome the problem at Wisma Menoreh Sampangan Hotel Semarang. In addition to the process of using bathroom equipment, a gas controller is needed in the bathroom, especially the ammonia and other gas levels in the bathroom . The bathroom control system at the Wisma Menoreh Sampangan Hotel in Semarang is currently considered ineffective, in the use of the bathroom equipment to hotel guests and hotel staff.The research method that I use is a Research and Development (R&D) research method that goes through stages of preliminary studies, planning, product development, testing, product design, product revision, and product testing. This system is made with the Arduino programming language. Based on the analysis, the ammonia gas detector in the Arduino-based bathroom can overcome the existing problems and help the hotel in controlling the bathroom, both to guests and hotel staff effectively and efficiently, as well as making it easier to manage bathroom rooms in the Hotel Wisma Menoreh Sampangan Semarang.